Non-marine ostracods of the Codó Formation (upper Aptian, Lower Cretaceous), Parnaíba Basin, NE Brazil: new biostratigraphic and paleoecological insights. (May 2022) - de Lima Barros, Cecília; Silva, Sílvia Clara; Machado, Lucas Lage; de Moraes Rios Netto, Aristóteles; Sames, Benjamin; Alves, Thamara Daniel; da Silva Júnior, Roberto Pereira
Abstract: The objectives of this work were to establish a biostratigraphic framework for the 1-UN-24-PI well, to suggest a new biostratigraphic approach to the study of the upper Aptian, Lower Cretaceous, and also to provide new paleoecological inferences based on ostracods for the Codó Formation in the Parnaíba Basin, NE Brazil. The described ostracod assemblages were recovered from 24 core samples, and are mainly represented by species of Harbinia . The identified species allowed recognition of the Harbinia spp. 201-218 Biozone. The last occurrences of Harbinia crepata and Harbinia micropapillosa are suggested as potential chronostratigraphic markers. A lagoon with brackish permanent waters and with permanent hydrologic connection (saline groundwaters) but intermittent direct connection to the sea is newly proposed as a paleoenvironmental model for the Codó Formation in the studied area. Highlights: Quantitative analysis of Codó Formation ostracods. Harbinia spp. 201-218 Biozone. Brackish lagoonal paleoenvironments.